Consumo de sustancias psicotrópicas y su incidencia en las relaciones interpersonales en un adolescente de 15 años de edad de la ciudad de Babahoyo - Bustamante Aguirre, Eduardo Braulio (2021)
This case study focused on the analysis of the factors that cause the consumption of psychotropic substances that affects the interpersonal relationships of a 15 year old adolescent from the city of Babahoyo. Study that was developed through the qualitative approach and cognitive behavioral therapy for its collection, it was made use of techniques such as the interview, observation, medical history and the application of the ASSIS test in which it focuses on assessing the degree of substance use consumption by the patient, such as alcohol, cannabis, marijuana, cocaine. Collection of information that will lead to the elaboration of a diagnosis using the Diagnostic and Statistical Manual of Mental Disorders together with the International Code of Diseases as F19.1 Criteria for substance abuse, which was considered to carry out the psychological intervention in the CETAD providing The adequate spaces for psychological assistance in the face of problems identified in the patient such as Consumption of psychotropic substances (abstinence) to which the relaxation technique was applied in order to reduce the withdrawal symptoms, interpersonal relationships were worked with a planning schedule or life project, together with a SWOT which will make it possible to clarify your life project, establishing short and long-term goals and addressing conflicts in the emotional bond between mother and child.